Model pengurusan sumber manusia dari perspektif Islam - Yusoff, Ab. Aziz; Ahmd Fadhil, Nur Fitriah; Shaari, Azmi (Sekolah Pembangunan Sosial, 2007)
Various models of human resource management from an Islamic perspective have been proposed and explored in Islamic, civilization. These models of human resource management have been proven to be efective and are therefore suitable to be followed. Human resource management from an lslamic perspective is believed to be the best and able to cater physiological, psychological and emotional needs and demands that is common to human beings. All these needs have to befuljilled in ensuring an eficient and effective utilization of human resources of organizations.In line with that basic assumption this article discusses a model of human resource management from an Islamic perspective as an alternative to conventional practices.